Synthesis and Biological Activity of Some 3,5-Diaryl-1-Benzothiazolopyrazoline Derivatives: Reaction of Chalcones with 2-Hyrazinobenzothiazoles - Vandana Sharma; K. V. Sharma (E-Journal of Chemistry)
A series of 3,5-diaryl-1-benzothiazolopyrazoline derivatives were synthesized by the reaction of appropriately substituted chalcones and 2-hydrazinobenzothiazole in ethanol. The synthesized heterocycles have been characterized on the basis of their chemical properties and spectroscopic data. These compounds were tested for biological activity against a variety of test organisms.